Hedging Dengan Tegas? Motif dan Praktik Indonesia di Laut China Selatan - Denny Indra Sukmawan; Rodon Pedrason (Intermestic: Journal of International Studies, 2023)
The research is about motives of hedging, and hedging in practices. Using empirical statistics and Indonesia as case study, we challenge a number traditional perspective that: (1) assert hedging is more suitable in a bipolar and power-deconsentrated system; (2) potrays hedging as ambiguous behavior. For sure and long, Indonesia has been practicing hedging. We agree that by hedging, Indonesia is closest to China economically, and getting closer to United States and his allies militarily. However, we also discover Indonesia has been sending signals to Great Powers other than China and United States to pay attention in the region, particularly South China Sea. And consequently by hedging, Indonesia contribute indirectly to enhance security dilemma condition within economic interdependence characteristics in the region.